1986
DOI: 10.1002/ar.1092140112
|View full text |Cite
|
Sign up to set email alerts
|

Gap junctions in rat sublingual gland

Abstract: Gap junctions were observed in rat sublingual gland to link serous cells to serous cells, mucous cells to mucous cells, and myoepithelial cells to myoepithelial cells. In addition to connecting homologous cells, gap junctions were present between conterminous serous and mucous cells. Since the rat sublingual gland is innervated solely by parasympathetic nerves, the presence of gap junctions between disparate secretory cell types raises the possibility that serous and mucous cells in this organ secrete simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Our immunohistochemical results contradict these earlier studies in that we found no positive spots for any CX between ductal cells. Our finding is supported by the results of conventional electron microscopic and freeze-fracturing studies by Nagato and Tandler (1986) [18] and Shimono et al (1980) [21] who found no GJs between ductal cells.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our immunohistochemical results contradict these earlier studies in that we found no positive spots for any CX between ductal cells. Our finding is supported by the results of conventional electron microscopic and freeze-fracturing studies by Nagato and Tandler (1986) [18] and Shimono et al (1980) [21] who found no GJs between ductal cells.…”
Section: Discussionsupporting
confidence: 89%
“…There have been many morphological investigations on GJs in the salivary glands [18,21,22,25]. GJs exist between acinar cells, between myoepithelial cells, and also between acinar cells and myoepithelial cells, but not between ductal cells [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many morphological investigations on GJs in salivary glands have been reported using electron microscopy and freeze-fracturing (Nagato and Tandler, 1986;Shimono et al, 1980;Nishihara, 1978;Sugiura, 1978;Young and Van Lennep, 1978). Moreover, Young and Van Lennep (1978) have suggested the presence of GJs between ductal cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that other factors might be involved in determining the efficiency of the neuro effector stimulation. One such factor could be the number of gap junctions which establish points of electrical cou pling between the effector cells so that stimulation may be spread to cells not directly innervated [5,24], The double AChE-positive and adrenergic innervation here described for five cebid genera occurs in all primate salivary glands studied so far, except for the human minor sublingual gland in which only the AChE-positive innerva tion is observed [10]. This type of innervation also occurs in the salivary glands of edentates [25] and possibly monotremes [261. as well as in the major sublingual gland of some rodents [27][28][29], The functional significance of this appar ently simpler type of innervation is not known, although it has been suggested that it might be related to a continuous and spontaneous secretion [7], It should be emphasized that the primate minor sub lingual gland, in spite of its uniform histological structure, predominantly made up of mucous secretory endpicces [ 18], is the most variable of the salivary glands regarding its innervation.…”
Section: Discussionmentioning
confidence: 99%